(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Listeria monocytogenes causes food-borne listeriosis in humans. Vegetables and animal-based foods facilitate transmission and contamination if mishandled. The research aims to isolate and identify L. monocytogenes from different food samples in the study area. The Food and Drug Administration, Bacteriology and Analytical Methods (FDA, BAM) were utilized to isolate L. monocytogenes. A total of 120 food samples were examined, consisting of 10 samples each of cabbage and fruit salads, as well as 20 samples each of fresh fish, meat, frozen chicken, ice cream, and yoghurt. These samples were purchased at random from various shops and markets in Yola at different times. The identification of isolates was performed using macroscopy, microscopy, biochemical tests, and polymerase chain reaction (PCR) amplification of the 16S rRNA gene. Out of the 120 food samples analyzed, 7 (5.8%) yielded growth of L. monocytogenes alongside other Listeria spp., with a high rate of L. monocytogene isolation from frozen chicken (3.5%) and cabbage (2.7%). Raw meat and yoghurt samples also yielded 1 (0.8%) growth of L. monocytogenes each. Through the examination of various food samples, it was identified that L. monocytogenes were present. This can be seen as an opportunity to take proactive measures to ensure the safety of consumers, particularly the elderly, immunocompromised individuals, and pregnant women in the study area. Minimizing the potential risk of L. monocytogenes can promote a healthier community.